2006
DOI: 10.1136/jcp.2004.025643
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of stent-induced stenosis in coronary and peripheral arteries

Abstract: These results show that coronary vessels are more prone to develop significant intimal hyperplasia and subsequent restenosis than internal iliac vessels. A better insight into how different arteries and arterial components behave is important in understanding and developing newer and better therapeutic measures for restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
0
31
0
1
Order By: Relevance
“…It has been shown that the iliac artery experiences more intimal hyperplasia than the coronary artery, but with less subsequent restenosis in porcine tests. The differences in restenosis rates between the two types of artery are not statistically significant (Krueger et al, 2006). Distal to the iliac arteries, the differences in restenosis rates between peripheral and coronary arteries is more evident.…”
Section: Introductionmentioning
confidence: 79%
“…It has been shown that the iliac artery experiences more intimal hyperplasia than the coronary artery, but with less subsequent restenosis in porcine tests. The differences in restenosis rates between the two types of artery are not statistically significant (Krueger et al, 2006). Distal to the iliac arteries, the differences in restenosis rates between peripheral and coronary arteries is more evident.…”
Section: Introductionmentioning
confidence: 79%
“…Also, D-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), attenuates the shear-induced activation of GalT-2, superoxide production and ICAM-1 expression (Yeh et al, 2001;Chatterjee, 1998). The triggering of an inflammatory reaction following activation of transcription factors NF-κB and AP-1 causes phenotypic modulation of medial vascular smooth muscle cells and their migration and subsequent proliferation in the intimal layer; increased extracellular matrix production by these vascular smooth muscle cells increases the volume of intimal tissue causing neointimal hyperplasia, ultimately leading to restenosis (Krueger et al, 2006;Mitra and Agrawal, 2006). The surface expression of Mac-1 or CD11/CD8 on human neutrophils is also stimulated by LacCer, ultimately leading to atherosclerosis.…”
Section: Ceramide and Cardiovascular Disordersmentioning
confidence: 99%
“…Although coronary and peripheral applications share several conceptual similarities in their preclinical evaluation, there are special considerations for peripheral devices with regard to model, anatomic location, and clinical application, for which supplementary references are provided. 41,98,161,208 Moreover, there is increasing complexity in the design of DES systems and the development of alternative endovascular treatments for ISR. Given that no set program or means for preclinical safety and efficacy evaluation can encompass all these endovascular technologies, this review seeks simplicity by focusing on DES systems commercially available or with published preclinical results.…”
mentioning
confidence: 99%